CLIMATE CHANGE & AGRICULTURE IN INDIA- EFFECTIVE IMPLEMENTATION OF NATIONAL MISSION FOR SUSTAINABLE AGRICULTURE - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
Climate change has been the most serious challenge affecting agriculture in India where direct effects of climate change are expected to be very harsh. India will need to produce estimated 320 MT of food grains by the year 2025. Acknowledging the significant role of Science & Technology, India has since 2008 established “National Action Plan on Climate Change” which includes “National Mission for Sustainable Agriculture [NMSA]” among eight missions. NMSA aims at developing technologies & innovative agricultural practices and strengthening the capacity of farming communities to cope effectively with both climatic variability and changes. Adaptation and mitigation potential is nowhere more pronounced than in India where agricultural productivity remains low and poverty, vulnerability & food insecurity remain high. Against this background this development perspective article attempts to highlight the impact of climate change on agriculture in general and in India in particular and suggests the priority areas to accelerate the process of effective implementation of NMSA launched on June 26, 2015.